2014
DOI: 10.1021/mz500310j
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Properties of Anionic Poly(ionic liquid)s with 1,2,3-Triazolium Counter Cations

Abstract: A series of anionic poly(ionic liquid)s with 1,2,3-triazolium counter cations are prepared by cation exchange between tailormade 1,3,4-trialkylated-1,2,3-triazolium iodides and a polystyrene derivative having pendant potassium bis(trifluoromethylsulfonyl)imide groups. The physical and ion-conducting properties of the resulting materials are compared to the parent potassium-containing polyelectrolyte based on 1H NMR, differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and broadband dielec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 23 publications
3
36
0
Order By: Relevance
“…Encouraged by the efficient post-functionalization reactions and the observed differences in hydrolysis rates ( Table 3 ), we wondered whether we could drastically stabilize compound [Na + ⊂2] by methylation of the triazoles. 36 At least in principle, the electron-withdrawing effect of the resulting triazolium on the orthoester bridgehead could lead to significantly reduced orthoester reactivity and pave the way towards applications of orthoester cryptands that require stability in water. As shown in Scheme 3a , treatment of [Na + ⊂2] with an excess of iodomethane furnished the corresponding bis-triazolium cryptate [Na + ⊂3] in 83% yield ( Scheme 3a , bottom).…”
Section: Resultsmentioning
confidence: 99%
“…Encouraged by the efficient post-functionalization reactions and the observed differences in hydrolysis rates ( Table 3 ), we wondered whether we could drastically stabilize compound [Na + ⊂2] by methylation of the triazoles. 36 At least in principle, the electron-withdrawing effect of the resulting triazolium on the orthoester bridgehead could lead to significantly reduced orthoester reactivity and pave the way towards applications of orthoester cryptands that require stability in water. As shown in Scheme 3a , treatment of [Na + ⊂2] with an excess of iodomethane furnished the corresponding bis-triazolium cryptate [Na + ⊂3] in 83% yield ( Scheme 3a , bottom).…”
Section: Resultsmentioning
confidence: 99%
“…Earlier literature has shown that the structure of the polymeric backbone and especially the position of the charge carrier strongly influence σ DC of PILs . TPILs obtained through copper(I)‐catalyzed azide‐alkyne 1,3‐dipolar cycloaddition (CuAAC) are particularly attractive since besides being readily obtained at the 10–50 g scale, the previous optimization of their structural parameters has afforded 1,2,3‐triazolium‐based ionenes having σ DC values matching the best PILs reported so far (i.e., σ DC > 10 −5 S/cm at 25 °C) . Poly(1,2,3‐triazole) 8 ( M n = 25.7 kDa, Ð = 1.71, Figure S1 in the Supporting Information), the common neutral precursor of TPILs 9 ‐ 15 , was prepared by CuAAC polyaddition of a C 11 ‐based α‐azide‐ω‐alkyne monomer .…”
Section: Resultsmentioning
confidence: 99%
“…We recently pioneered a new class of PILs possessing 1,2,3‐triazolium groups by merging different polymerization methods with copper‐catalyzed alkyne–azide cycloaddition (CuAAC), N ‐alkylation of 1,2,3‐triazoles, and optional anion metathesis . The broad structural design afforded by CuAAC allows access to a wide library of highly functional 1,2,3‐triazolium‐based PILs and ILs . This work presents the synthesis of ion‐conducting EANs having covalently linked 1,2,3‐triazoliums.…”
Section: Introductionmentioning
confidence: 99%